The direct incidence of corporate income tax on wages - Wiji Arulampalam; Michael P. Devereux; Giorgia Maffini (Institute for the Study of Labor (IZA), 2010)
We examine the extent to which taxes on corporate income are directly shifted onto the workforce. We use data on 55,082 companies located in nine European countries over the period 1996-2003. We identify this direct shifting through cross-company variation in tax liabilities, conditional on value added per employee. Our central estimate is that the long run elasticity of the wage bill with respect to taxation is -0.093. Evaluated at the mean, this implies that an exogenous rise of 1 in tax would reduce the wage bill by 49 cents. We find only weak evidence of a difference for multinational companies.
Keywords: H22; H25; J50; 330; income tax; wage bargaining; effective incidence; Unternehmensbesteuerung; Körperschaftsteuer; Lohnniveau; Europa